CURRENT ASPECTS OF TREATMENT AND COMPLICATIONS OF COVID-19 IN CHILDREN WITH ALLERGIC DISEASES (LITERARY REVIEW) (World Bulletin of Public Health, 2023)
Children with comorbidities such as developmental disorders, endocrine system problems, allergic diseases, cancer pathology, immunodeficiency, the disease is more severe than in healthy children. Children have similar symptoms of coronavirus to adults - fever, conjunctivitis, muscle pain, gastrointestinal disorders. Scientists believe, she added, that one complication of coronavirus in children is multiviral syndrome. It's a delayed immunologic response to COVID 19. It's a condition that can occur in a child whether the disease is symptomatic or asymptomatic